A chamada “conferência da Citânia”: revisitando um evento pioneiro da Arqueologia Portuguesa - Guerra, Amílcar (Estudos Arqueológicos de Oeiras, 2022)
Some complementary aspects of an important and well‑known scientific event of the 19th century, the so called “Conferência da Citânia” are presented. Firstly, the ups and downs of its preparation and the role of its promoters are discussed, with special emphasis on Martins Sarmento and Pereira Caldas. Secondly, the most famous participants are listed, identifying some aspects that justified the presence in this conference of some relevant figures of the archaeological research in Portugal; a particular attention to some guests who could not be present. Finally, mention is made to the echoes of the event in the press and to the balance of the conference, especially Sarmento’s more pessimistic perspective, as opposed to the vision of other participants.